2021
DOI: 10.1177/15385744211023291
|View full text |Cite
|
Sign up to set email alerts
|

Portal Vein Aneurysm Treated With Trans-Jugular Intrahepatic Porto-Systemic Shunt

Abstract: Portal vein aneurysm (PVA) is a rare entity that can lead to hemorrhage or thrombosis. Although there is no standard treatment, most cases can be managed conservatively; intervention is reserved for symptomatic or enlarging aneurysms. For patients who are not surgical candidates due to cirrhosis and portal hypertension, endovascular creation of a trans-jugular intrahepatic porto-systemic shunt (TIPS) is an option to reduce portal venous pressure. This report describes a case of an enlarging PVA successfully tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The treatment may lead to other complications such as hepatic encephalopathy and liver failure 15 , 16 . Analysis of the reasons shows that a large amount of portal blood is directly shunted into the vena cava, causing ischemia and atrophy of the liver, inducing or aggravating the decline of liver function, resulting in liver function failure.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment may lead to other complications such as hepatic encephalopathy and liver failure 15 , 16 . Analysis of the reasons shows that a large amount of portal blood is directly shunted into the vena cava, causing ischemia and atrophy of the liver, inducing or aggravating the decline of liver function, resulting in liver function failure.…”
Section: Discussionmentioning
confidence: 99%
“…The patient remained asymptomatic for 72 mo[ 45 ]. Dunlap et al [ 46 ] also used a TIPS successfully to treat a PVA resulting from portal hypertension and liver cirrhosis. Kohlbrenner et al [ 47 ] demonstrated transhepatic pharmacomechanical thrombolysis of a large thrombosed PVA.…”
Section: Etiology Multimodal Imaging and Current Managementmentioning
confidence: 99%